Hot topics on UV filter ingredients. (October 2011) - Andreassi, Marco; Anselmi, Cecilia
The production of sunscreens is regulated by laws and lists, constantly updated on the basis of scientific information. Most advanced countries have regulatory bodies that publish and update the list of authorized substances. Inorganic filters, zinc oxide and titanium dioxide are often used as nanostructured forms. Nanoparticles have been the subject of technological studies aimed at improving efficacy and safety. The organic ingredients are able to absorb UV radiation on a selective or broad spectrum. The latter is preferable given the role of UVA radiation in skin carcinogenesis. The organic filters may interact with epidermal proteins and induce sensitization. They can also be absorbed, causing systemic effects. In addition, some organic ingredients, such as avobenzone, may undergo photodegradation, needing special formulation requirements.